PENGARUH ORIENTASI PASAR, KUALITAS LAYANAN, KEPUASAN KONSUMEN DAN KEUNGGULAN BERSAING TERHADAP KEPUTUSAN PEMBELIAN PADA KING PERABOT KOTA PINANG - Bagus Susanto; Elvina Harahap; Ali Sahputra; Desmawati Hasibuan (LP2M Universitas Bina Bangsa, 2021)
This study aims to determine the effect of market orientation, service quality, customer satisfaction and competitive advantage on the purchasing decision of the King of Furniture in Kota Pinang.. Data collection in this study was conducted through a survey approach with descriptive research type by distributing questionnaires to 35 respondents, while the population used in this study was On the King of Pinang City Furniture. The data technique was done by interview, questionnaire and documentation study. The data analysis tool used in this study was SPSS (Statistical Product Software Solution). The results showed that partially (t test) it is known that Market Orientation has a significant effect on Purchasing Decisions at the King of Furniture in Pinang City. Service Quality has a significant effect on Purchasing Decisions at the King of Pinang City Furniture, Consumer Satisfaction has a significant effect on Purchasing Decisions at the King of Pinang City Furniture.Then Competitive Advantage has a significant effect on Purchasing Decisions at the King of Pinang City Furniture. , Service Quality, Customer Satisfaction and Competitive Advantage have a significant effect on Purchasing Decisions at the King of Pinang City Furniture through testing the coefficient of determination (R Square) 7.30% which means that Market Orientation, Service Quality, Customer Satisfaction and Competitive Advantage have a significant effect on Purchasing Decisions. , 32% the remaining 4.70% from other variables not examined in this study.